Combination of low-pressure UF membranes with conventional water treatment systems - Karali, I; Cakmakci, M.; Koyuncu, I; Demir, A.; Karadag, D. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2017)
The purpose of the study was to improve drinking water quality of conventional treatment processes by combining with UF-membrane systems. Performances of two membrane systems were evaluated in two different full-scale conventional water treatment plants in Istanbul. Low-pressure UF membranes were combined after settling and filtration units of Buyukcekmece and Emirli water treatment plants. Low-pressure UF systems were operated under vacuum and pressure conditions. The experimental results indicated that combining UF systems enhanced drinking water quality with respect to turbidity, TOC and UV254 removal. In all cases, vacuum-driven UF membranes provided higher treatment performance and low energy consumption comparing to pressure-driven system. Combination with UF membranes also reduced disinfection by-products.
Keywords: drinking water; low-pressure UF; conventional treatment; turbidity; TOC; NATURAL ORGANIC-MATTER; DRINKING-WATER; FOULING CONTROL; SURFACE-WATER; ULTRAFILTRATION; REMOVAL; TRIHALOMETHANES; NANOFILTRATION; COAGULATION; PLANT; Environmental Sciences & Ecology